Evidence of metal-semimetal-transition from Cu2TlSe2 to Cu2TlTe2. (May 2017) - Li, Xiao; Lv, Yang-Yang; Pang, Bin; Zhang, Bin-Bin; Cao, Lin; Yao, Shu-Hua; Zhou, Jian; Chen, Y.B.; Dong, Song-Tao; Zhang, Shan-Tao; Lu, Ming-Hui; Chen, Yan-Feng
Graphical abstract: Highlights: Cu2 TlX2 (X = Se, Te) single crystals were grown by the vertical Bridgman method. Electrical measurements verify that Cu2 TlSe2 is a metal, but Cu2 TlTe2 is a semimetal. Electronic band structure verifies that non-stoichiometric Cu2 TlTe2 is a semimetal. Abstract: Transition metal compounds with quasi-two-dimensional structure demonstrate a series of un-precedent quantum phases, such as topological insulator, topological phase transition under thermal/pressure stimuli, which is attributed to delicate interplay among interlayer coupling, spin-orbit coupling and stoichiometry. Here, Cu2 TlSe2 and Cu2 TlTe2 crystals were successfully synthesized by Bridgeman method. Highly crystalline quality of these samples is verified by X-ray diffraction and microstructural characterization. Temperature-dependent-Hall-resistivity shows that Cu2 TlSe2 is hole-like and Hall resistivity is in-sensitive to temperature; while Hall resistivity of Cu2 TlTe2 is positive at room temperature and change to negative at 30 K. Combined experimental results and electronic band structures calculated by first-principles method, it is revealed that Cu2 TlSe2 is a metal, but Cu2 TlTe2 is a semi-metal. This work demonstrates the rich physical phases of layered transition metal compounds under the interplay among interlayer coupling, spin-orbit coupling and stoichiometry.